THE TOPIC OF THE THESIS IS "ETHNIC DIFFERENCES IN HYPERTENSIVE DISORDERS IN PREGNANCY AND STRATEGIES TO ELIMINATE THEM" - Ulugʻova Muxlisa; Egamova Feruza; Axtamova Nilufar Akbarjanovna (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2025)
Hypertensive disorders in pregnancy (HDP), including gestational hypertension, preeclampsia, and eclampsia, represent a significant global health challenge, contributing to maternal and fetal morbidity and mortality. This thesis examines ethnic differences in the prevalence, severity, and outcomes of HDP, with a particular focus on elevated risks among non-Hispanic Black women compared to other groups such as non-Hispanic White, Hispanic, and Asian/Pacific Islander women. Drawing from epidemiological data, the analysis highlights disparities rooted in social determinants of health, genetic factors, and healthcare access. Strategies to mitigate these disparities emphasize primordial prevention, equitable healthcare practices, and innovative interventions like low-dose aspirin prophylaxis, postpartum monitoring, and community-based participatory research. Through a systematic literature review, this work underscores the need for multi-sectoral collaboration to address structural racism and improve maternal health equity. The findings advocate for targeted public health initiatives to reduce HDP-related disparities and enhance long-term cardiovascular outcomes across ethnic groups.